Growth Hormone Receptor Antagonist Transgenic Mice Are Protected From Hyperinsulinemia and Glucose Intolerance Despite Obesity When Placed on a HF Diet - Yang, Tianxu (Endocrinology, 2015)
Reduced GH levels have been associated with improved glucose metabolism and increased longevity despite obesity in multiple mouse lines. However, one mouse line, the GH receptor antagonist (GHA) transgenic mouse, defies this trend because it has reduced GH action and increased adiposity, but glucose metabolism and life span are similar to controls. Slight differences in glucose metabolism and adiposity profiles can become exaggerated on a high-fat (HF) diet. Thus, in this study, male and female GHA and wild-type (WT) mice in a C57BL/6 background were placed on HF and low-fat (LF) diets for 11 weeks, starting at 10 weeks of age, to assess how GHA mice respond to additional metabolic stress of HF feeding. On a HF diet, all mice showed significant weight gain, although GHA gained weight more dramatically than WT mice, with males gaining more than females. Most of this weight gain was due to an increase in fat mass with WT mice increasing primarily in the white adipose tissue perigonadal depots, whereas GHA mice gained in both the sc and perigonadal white adipose tissue regions. Notably, GHA mice were somewhat protected from detrimental glucose metabolism changes on a HF diet because they had only modest increases in serum glucose levels, remained glucose tolerant, and did not develop hyperinsulinemia. Sex differences were observed in many measures with males reacting more dramatically to both a reduction in GH action and HF diet. In conclusion, our findings show that GHA mice, which are already obese, are susceptible to further adipose tissue expansion with HF feeding while remaining resilient to alterations in glucose homeostasis.